2019
DOI: 10.1519/jpt.0000000000000216
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Predictors of Comfortable and Fast Gait Speed in Community-Dwelling Older Adults

Abstract: Background/Purpose: To identify the unique predictors of comfortable and fast gait speed in community-dwelling older adults using measures of physical performance (eg, lower extremity strength and balance), self-reported balance confidence, and global cognitive function. Methods: Demographic information was collected from 60 healthy, community-dwelling older adults older than 60 years. Participants completed the following assessments: Mini-Mental State … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 48 publications
0
25
0
1
Order By: Relevance
“…By focusing on muscle performance and lean mass of the entire lower extremity, rather than isolated muscles, we would contend that our approach better reflects measures that may typically be used in a clinical setting. We should concede, however, that while the absolute and rapid strength measurements utilized herein explained roughly 25% of the variance in fast gait speed, other previous studies have demonstrated stronger prediction [9,27,47]. For example, Clark et al [9] reported that the combination of age, muscle and fat mass variables, and the rate of electromyographic rise accounted for 72.4% and 43.7% of the variance in fast gait speed for men and women, respectively.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…By focusing on muscle performance and lean mass of the entire lower extremity, rather than isolated muscles, we would contend that our approach better reflects measures that may typically be used in a clinical setting. We should concede, however, that while the absolute and rapid strength measurements utilized herein explained roughly 25% of the variance in fast gait speed, other previous studies have demonstrated stronger prediction [9,27,47]. For example, Clark et al [9] reported that the combination of age, muscle and fat mass variables, and the rate of electromyographic rise accounted for 72.4% and 43.7% of the variance in fast gait speed for men and women, respectively.…”
Section: Discussionmentioning
confidence: 53%
“…We sought to study the isometric squat rather than isolated joint movements because we felt that analysis of a lower-extremity, multi-joint movement involving the activation of dozens of muscles would better characterize fast gait performance. Squatting movements are also commonly utilized in resistance training interventions [37] and physical therapy and rehabilitation clinics [27]. By focusing on muscle performance and lean mass of the entire lower extremity, rather than isolated muscles, we would contend that our approach better reflects measures that may typically be used in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current literature recognizes a number of influencing variables on gait speed including balance [14][15][16][17], lower extremity muscle strength [14,15,18,19], cognition [20][21][22], and demographic characteristics (e.g. age) [17].…”
Section: Introductionmentioning
confidence: 99%
“…While each clinical parameter may assess a specific aspect of lower-body functioning, achieving a high performance on any one task requires adequate performance on the other measures. For example, being able to quickly walk 8 ft requires a person to have sufficient lower body strength to move themselves forward and be able to maintain their balance during each phase of the gait cycle ( Mantel et al, 2019 ; Shubert et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%